2014
DOI: 10.3349/ymj.2014.55.3.792
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound-Guided Trigger Point Injection for Myofascial Trigger Points in the Subscapularis and Pectoralis Muscles to Post-Mastectomy Patients: A Pilot Study

Abstract: PurposeTo investigate the therapeutic effectiveness of ultrasound (US)-guided trigger point injection for myofascial trigger points (MTrPs) in the internal rotator muscles of the shoulder in post-mastectomy patients.Materials and MethodsThis pilot study was a non-controlled, prospective, clinical trial. Nineteen post-mastectomy patients with a diagnosis of at least one active MTrP in the subscapularis and/or pectoralis muscles were included. We performed trigger point injections into the subscapularis muscle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Ultrasound-guided injections in breast cancer survivors are also reported scarcely in the literature. Trigger point injections in myofascial pain syndrome (18) and intercostobrachial nerve blocks (28) are successfully performed without complications. Realtime ultrasound helps the physician to precisely place the needle and correctly deliver the medication to the targeted site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound-guided injections in breast cancer survivors are also reported scarcely in the literature. Trigger point injections in myofascial pain syndrome (18) and intercostobrachial nerve blocks (28) are successfully performed without complications. Realtime ultrasound helps the physician to precisely place the needle and correctly deliver the medication to the targeted site.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies investigating the intervention techniques in limited number of patients. Stellate ganglion block in patients with lymphedema (17), ultrasound-guided trigger point injections in myofascial pain syndrome (18), and intraarticular shoulder injection in patients with frozen shoulder are few examples for interventional treatment approaches in the field of breast cancer related upper limb problems (19).…”
mentioning
confidence: 99%
“…Our trial is in line with two other tender point block studies in persistent postsurgical pain, with respect to the analgesic effect of LA in patients with post-thoracotomy pain 17 and persistent pain after breast cancer surgery. 18 However, neither of these studies were placebo-controlled or used neurophysiological tests to validate the findings, making the results difficult to interpret. Other non-controlled nerve block studies in PIPP-patients have also shown analgesic responses with LA and have been used for identifying patients for neurectomy, 19 neurolysis 20 or as a treatment on its own.…”
Section: Nerve Blockadementioning
confidence: 99%
“…Initial studies have successfully used the Pecs block perioperatively for pain management in the immediate postoperative period after breast cancer surgery . However, the Pecs block has not been evaluated in patients with PPBCS although a version of the Pecs block has been used as a supplemental block in 6 of 19 patients that also received LA blockade of myofascial trigger points in the subscapularis muscle . In fact, the purpose of that study was to examine the effects of the subscapularis block and the indication for the Pecs block was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, the Pecs block has not been evaluated in patients with PPBCS although a version of the Pecs block has been used as a supplemental block in 6 of 19 patients that also received LA blockade of myofascial trigger points in the subscapularis muscle. 11 In fact, the purpose of that study was to examine the effects of the subscapularis block and the indication for the Pecs block was unclear. Also, the patients received a variable number of blocks on a weekly basis making it difficult to determine the effects of a single LA block, per se.…”
Section: Introductionmentioning
confidence: 99%